Syariah Self-Efficacy, Competency Certification, and Digital Literacy on Work Readiness of Expertise Program Students Mediated by Field Work Practices in The Islamic Concept - Faeni, Ratih Puspitaningtyas; Faeni, Dewi Puspaningtyas (UPT Publikasi Ilmiah UNISBA, 2025)
This study examines the impact of self-efficacy, competency certification, and digital literacy on the work readiness of students enrolled in expertise programs, with a focus on the mediating role of field work practices within an Islamic educational context. 250 students participated in the study by filling out questionnaires and participating in focus groups. The type of research was quantitative research with 250 respondents as simple random sampling based on Slovin formula. SEM-PLS model's statistical tests for validity and reliability were applied to both the outer and inner models. The findings indicate that higher levels of self-efficacy and competency certification significantly enhance students' perceived work readiness. Additionally, digital literacy emerged as a critical factor, particularly when coupled with practical fieldwork experiences that align with Islamic values and principles. The study underscores the importance of integrating these elements to better prepare students for the workforce, providing valuable insights for educators and policymakers in Islamic educational settings. Additionally, a combination of self-efficacy, competency certification, and digital literacy has a 55.20% influence on work readiness.